2020
DOI: 10.1021/acs.jpcb.0c03207
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Phase Separation of Viologen Bistriflimide/Benzene Mixtures: Role of the Dual Ionic and Organic Nature of Ionic Liquids

Abstract: Liquid–liquid phase separation occurs at room temperature when mixing an excess of benzene with solid viologen bistriflimide salts with various alkyl side-chain lengths. A liquid phase composed of (almost) pure benzene is above the other sponge-like liquid phase with salt absorbed in benzene. Nuclear magnetic resonance experiments indicate that the mole ratio of benzene/salt in the sponge-like phase remains unchanged upon varying the amounts of (nonexcessive) salt or benzene. Moreover, the benzene/viologen sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Another possible future route to investigate the benzene solubility in ILs involves changing the cationic alkyl side-chain length. Our previous study demonstrates that in the benzene/IL mixtures where the cations possess a relatively long alkyl side chain, the benzene molecules solvated in nonpolar domains composed of alkyl side chains dominantly contribute to benzene solubility, and the π-stacking feature is negligible. Another experiment also indicates that when the alkyl chain is long enough, the liquid phase–phase separation can disappear at a certain temperature, and the temperature dependence of solubility can vary with alkyl side-chain length.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Another possible future route to investigate the benzene solubility in ILs involves changing the cationic alkyl side-chain length. Our previous study demonstrates that in the benzene/IL mixtures where the cations possess a relatively long alkyl side chain, the benzene molecules solvated in nonpolar domains composed of alkyl side chains dominantly contribute to benzene solubility, and the π-stacking feature is negligible. Another experiment also indicates that when the alkyl chain is long enough, the liquid phase–phase separation can disappear at a certain temperature, and the temperature dependence of solubility can vary with alkyl side-chain length.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…[133] performed both NMR experiments and all-atom MD simulations on a set of mixtures of benzene and viologen bistriflimide salts [CmbpCn)2][CF3SO2)2N] with m and n being the numbers of carbon atoms on the two alkyl side chains. The viologen salts are crystal at room temperature but also exhibit ILC and NSL phases at higher temperatures, as common ILs do [133].…”
Section: Liquid-liquid Phase Separation Of Il/benzene Mixturementioning
confidence: 99%
“…It is widely recognized that extraction mechanisms in conventional diluents rely heavily on the self-assembly of the extractant molecules in supramolecular aggregates, and some studies have shown that different kind of solutes and surfactants can self-assemble into aggregates of different shapes in ILs. Additionally, some studies revealed that enhanced extraction efficiency in ILs without ion exchange can be attributed to variations in structural properties. ,, Consequently, it is crucial to further investigate the relationship between structure and extraction efficiency in ILs, and to do so, a thorough understanding of the physicochemical interactions between the extractant and solvent molecules is essential.…”
Section: Introductionmentioning
confidence: 99%